De um porto a outro: um navegar histórico no multiverso da vida e obra de João Cabral de Melo Neto - Galve, Fernanda Rodrigues (2012)
This thesis is a navigation in the multiplicity of João Cabral de Melo Neto´s life and work. The anchorage of the research is in the visibility of the poetic work with the approach of its meanings and mediations in the sea of History. It attempts to reflect how the ability of artistic praxis holds itself a political and historical dimension. The thesis presents the story of a man that when experiences the literature´s fascinations and challenges, adds them to the reflexion in his dialog with several societies and friends. We have an anthology of great moments of the author (either as a diplomat, critic, historian, printer and man of words). A true nautical letter on art, literaly creation, societies, politics and, of course, life. This thesis elapses the life of a man who records and "dwells time" and learns which is lived in poetic words